1998
DOI: 10.1080/01904169809365529
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal colonization and nutrient uptake of dry bean in manure and compost manure treated subsoil and untreated topsoil and subsoil

Abstract: Eroded or leveled Portneuf silt loam soils (coarse-silty mixed mesic Durixerollic Calciorthid) have been restored to topsoil productivity levels by manure application, but not by other organic sources such as cheese whey. In dry bean (Phaseolus vulgaris L. cv. Viva), only soil organic matter and Zn concentration of leaf tissue correlated with improved yields. Manure application could potentially increase or decrease mycorrhizal colonization depending on which factors dominate. Manured and unmanured soils from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 29 publications
1
19
4
Order By: Relevance
“…This con®rms observations by Tarkalson et al (12) with sweet corn and wheat in 1997. However, results with dry bean in the ®eld were opposite those from the greenhouse pot experiment using freshly exposed subsoil (11). The con¯icting accounts of greenhouse and ®eld colonization for dry bean could be due to a decreased effectiveness of manure over time.…”
Section: Mycorrhizal Colonizationcontrasting
confidence: 42%
See 3 more Smart Citations
“…This con®rms observations by Tarkalson et al (12) with sweet corn and wheat in 1997. However, results with dry bean in the ®eld were opposite those from the greenhouse pot experiment using freshly exposed subsoil (11). The con¯icting accounts of greenhouse and ®eld colonization for dry bean could be due to a decreased effectiveness of manure over time.…”
Section: Mycorrhizal Colonizationcontrasting
confidence: 42%
“…Boswell et al (10) found the degree of AM infection of corn positively correlated with growth and yield. Tarkalson et al (11) observed increased AM colonization of dry bean roots from dairy manure applied at time of planting to freshly exposed subsoil samples in the greenhouse but decreased colonization in ®eld-grown sweet corn and wheat from manure applied to soils six years earlier (12). Increases in nutrient uptake and yield from arbuscular mycorrhizal (AM)-plant symbiosis are well documented (13,14,15,16).…”
Section: Introduction Organic Matter Manure and Mycorrhizal Colonizmentioning
confidence: 96%
See 2 more Smart Citations
“…Understanding the effect of designed biochars on soil microbiology may have a substantial practical impact on our ability to improve the productivity of eroded calcareous soils, whose lack of organic C inhibits microbial activity (Tarkalson et al, 1998). In this case, the switchgrass biochar employed is one developed specifically for its low pH, which potentially will help neutralize the target soil's alkaline character and further enhance microbial contributions.…”
Section: Introductionmentioning
confidence: 99%